Determination of Some Physicochemical and Microbiological Properties of Rosehip Marmalades - Ayşe Özbey; Nilgün Öncül; Kader Tokatlı; Metin Yıldırım; Zeliha Yıldırım (Turkish Journal of Agriculture: Food Science and Technology)
In this study, some physicochemical and microbiological properties and antioxidant capacity of 30 rosehip marmalades produced in Tokat province by industrial or regional methods were determined. pH, water activity, viscosity, total dry content, total soluble solids, total ash, total sugar content, total ascorbic acid content and Hunter values (L*, a* and b*) were carried out to determine the physicochemical properties of samples and the means were 4.12, 0.881, 2501.6 cP, 56.12%, 56.86, 0.935%, 50.24 g/L, 173.43 mg/100g, 30.89, 10.90 and 15.11, respectively. The count of S. aureus, total and fecal coliform was not detected in any samples. The total phenolic content and TEAC were performed to investigate antioxidant capacity and the average values were 921.62 mg GAE/100 g and 66.93 µmol trolox/g.